Citra Tubuh (Body Image) Remaja Perempuan - Amalia, Lia (Musawa Jurnal Studi Gender dan Islam, 2007)
A socio,cultural component has long been blamed for the excessive concern with the appearance of women. Typically, the media is blamed for creating an impossible thin ideal as a model for women to emulate, and such images in magazines and on TV have been cast as the cause of widespread use of excessive dieting and eating disorders to achieve the "unachievable". The onset of theses two diseases typically occur during early adolescence or early adulthood when most young women are not only susceptible to cultural pressure for thinness and whiteness but also likely to be heavily involved with, and influenced by the mass media. This point may help explain how cultural images of one's reference group, may constitute an inescapable group that can have negative consequences as it is incorporated into local culture. The susceptibility to these pressures and influences from the media is believed to be heightened because of the fact that intense preoccupied with appearance and identity development characterizes adolescent girls.